2019
DOI: 10.1097/jsm.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Flexibility and Low Back Pain in Female Adolescent Gymnasts

Abstract: Objective: To determine the relationship between low back pain (LBP), flexibility, and individual demographic characteristics in competitive adolescent female gymnasts. Design: Cross-sectional observational study. Setting: Gymnastics facilities in Colorado. Participants: Six- to 18-year-old gymnasts who participate in the USA Gymnastics Women's Artistic Junior Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Another important finding was that the prevalence of SP increased with chronological age, according with hypothesis (b). A similar evolution has been found in previous studies [ 24 , 31 , 46 ]. This finding has important implications for the introduction of SP education programs in secondary education.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another important finding was that the prevalence of SP increased with chronological age, according with hypothesis (b). A similar evolution has been found in previous studies [ 24 , 31 , 46 ]. This finding has important implications for the introduction of SP education programs in secondary education.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, one interesting finding was that the relationship between age and SP was stronger in FS that in MS, although in general no differences were found in the prevalence of pain reported by the adolescents according to sex. A possible explanation for this may be that menarche is the most predictive demographic or medical history factor associated with LBP according to previous data [ 31 ]. FS hormones, particularly estrogens, increase after menarche, inducing changes in the girls’ bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies included artistic gymnasts [21,22], 2 studies included rhythmic gymnasts [23,24], 11 studies simply used the term "gymnasts" [1,2,4,9,[25][26][27][28][29][30][31]. With regard to the level of gymnasts, 6 studies included gymnasts classified as national team level [9,21,22,[29][30][31], 2 studies involved gymnasts from clubs affiliated with a national federation [1,23], 1 study involved gymnasts from a precompetitive level [25], 3 studies used competitive-level gymnasts [4,26,28], 2 studies used a mixed group of gymnasts [2,27] and 1 study included gymnasts attending a course and the level was unclear [24].…”
Section: Gymnastic Genre and Levelmentioning
confidence: 99%
“…Within artistic gymnastics the floor apparatus is associated with the greatest injury risk [6][7][8]. Gymnastic movements rely heavily on integration via the kinetic chain with skills such as handsprings and walkovers involving spine and hip extension and shoulder hyperflexion [9]. Injury surveillance of 3 Olympic games has identified that the lower limb (62.8%), trunk (23.1%) and upper limb (14.1%) as the regions most susceptible to injury with the ankle the most prominent location (21.8%) [10].…”
Section: Introductionmentioning
confidence: 99%